Concept Analysis of Emotion Regulation in Teenagers - Anggorowati; Hadiyanto, Nor; Dwidiyanti, Meidiana (Alta Dharma Publisher, 2022)
Background: Teenager is a period of transition from childhood to adulthood marked by essential changes in puberty, psycho-social, cognitive, emotional, and educational. Therefore, emotion regulation strategies are fundamental to controlling negative emotions in a teenager. Objective: The study aimed to describe the concept of emotion regulation in a teenager. Method: The literature review used online databases such as ScienceDirect, Scopus, Emerald Insight, Springer Link, and Clinical Key with keywords emotion regulation and adolescent and concept analysis. Result: Antecedents of the concept of emotion regulation in adolescents: self-control, mental boundaries, and self-determination. Concept attributes situation selection, situation modification, attention distribution, cognitive change, and response modulation. Consequences of the concept: success in controlling emotions in adolescents and the effectiveness of emotion regulation. Conclusion: The concept of emotion regulation is also used in examining the effect of emotion regulation on forgiving behavior in junior high school students. Recommendation: Researchers hope that other studies can carry out these actions/interventions on children and parents